FARKLI SICAKLIKLARDAKİ PARALEL JET AKIŞLARINDA NANOAKIŞKAN VE DÖNEL AKIŞIN AKIŞ VE ISIL KARIŞIM DAVRANIŞLARININ SAYISAL VE DENEYSEL OLARAK İNCELENMESİ - GÜR, MUHAMMED (Fırat Üniveristesi, 2018)
Günümüzde enerjinin önemi gün geçtikçe daha da artmaktadır. Enerjiyi daha verimli kullanabilmek çok daha önem arz etmektedir. Dönmeli akışlar ısı transferi gibi önemli konularda pek çok yarar sağlamaktadır. Bu çalışmada, farklı sıcaklıklardaki dönmeli jet akışlarının sınırlandırılmış bir kanal içerisindeki termofiziksel özellikleri deneysel ve sayısal olarak incelenmiştir. Çalışmanın deneysel kısmı için bir deney seti imal edilmiş ve sayısal kısmı da Large Eddy Simulation türbülans modeli kullanılarak modellenmiştir. Akışkan olarak su ve nanoakışkan kullanıldığı analizlerde dönmeli paralel jet modeli kullanılmıştır. Analizler jetler arası sıcaklık farkı ve momentum oranının fonksiyonu olan altı farklı sınır şartı için yapılmıştır. Deneysel ve sayısal veriler analiz edilirken iki tür yaklaşım uygulanmıştır. Birinci yaklaşımda farklı sıcaklıklardaki jet akışlarının kanal boyunca ısıl karışım davranışları irdelenmiştir. İkinci yaklaşımda ise belirlenen çalışma parametrelerinin dönmeli jetlerin akış davranışları üzerindeki etkileri kapsamlı bir şekilde ele alınmıştır. Sonuçlar, bütün çalışma parametrelerinde dönmeli jetler arası sıcaklık farkı arttıkça ve nanoakışkan derişimi arttıkça ısıl karışımın iyileştiğini göstermiştir. Dönmeli Jet momentum oranları değiştikçe ısıl karışım davranışları önemli değerde değişmiştir. Ayrıca incelenen bir diğer parametrede ise dönme aparatının açısı arttıkça ısıl karışımın veriminin arttığı anlaşılmıştır. Sayısal veriler ile deneysel veriler birbiriyle uyuşmaktadır.

Today, the importance of energy is increasing day by day. It is even more important to be able to use energy more efficiently. Swirling flows provide a number of benefits in important applications such as heat transfer. In this work, thermophysical properties of turbulent jet flows at different temperatures in a confined channel have been investigated experimentally and numerically. An experimental setup for the experimental part of the work was produced and the numerical part was modeled using the Large Eddy Simulation turbulence model. In analyzes where water and nano-fluid are used as fluids, a swirling parallel jet model is used. The analyses were carried out for six different boundary conditions, functioning as temperature difference and momentum ratio between jets. Three types of approaches have been applied when analyzing experimental and numerical data. In the first approach, the thermal mixing behaviors of jet flows at different temperatures along the channel are investigated. In the second approach, the thermal oscillation behavior in the turbulent region where the thermal mixing is effectively performed is analyzed and it has been determined that these oscillations create a thermal stress-induced risk for the channel walls. In the third approach, the effects of the determined operating parameters on the flow behavior of the swirling jets have been extensively discussed. The results show that the thermal mixture improves as the temperature difference between the swirling jets increases and as the nanofascial concentration increases for all operating parameters. As the rotational jet momentum ratios change, the thermal mixing behaviors have changed significantly. In another parameter that is examined separately, it is understood that the efficiency of the thermal mixture increases as the angle of the Swirling apparatus increases. Numerical data and experimental data agree with each other.
Numerical and experimental investigation of flow and thermal mixing behaviors of nanofluid and swirling flow in parallel jet flows at different temperatures
Keywords: Makine Mühendisliği